نادیاری زمانی كوردی بەپێی زمانەوانی بەرانبەری - قادر, ابوبكر عمر (Sulaimani Journal for Humanities, 2018)
This research entitled Passive Voice in contrastive linguistics a descriptive applied study of the passife voice structure sentence in Kurdish & Arabic. It is an updating and developing of comparative linguistics with precision and specification in describing and explaining the language components and its phonetic, morphological, syntactic, and semantic levels in these unrelated languages in terms of origins. These levels are the basis for the modern contrastive linguistics. گۆڤاری زانکۆی سلێمانی/ بەشی )B )زانستە مرۆڤایەتییەکان ژمارە )85( تشرینی یەکەمی8105 11 Thus, to learn and acquire languages necessitate the use of contrastive analysis as an integral approach to the study of syntactic phenomena, one of which is the passive voice verb structure. This research compares and contrasts the structure of this phenomenon in the sentences of the central Kurdish dialect against the Arabic sentences through the structural change from the active sentence to the passive sentence, which requires changes in the structure of the latter. Each of these languages takes a different pathway. In Kurdish there is a mathematical pattern in past and present tenses using the passive morpheme r at the end of the verb plus a indicating the past and E morpheme to indicate the present? Thus, the structure looks like (verb stem + r + a in the past + e for the present). For the present in the informative sentence. For the perfect, the phonetic or morphormic segments are added to the distant past, the near past, the continuous, and the remote past. Also, to the past without a difference in their various structures, which in turn help to reduce the difficulty of learning and understanding Kurdish. The changing process of active into passive in Arabic depends on a replacement of the triple- lettered verbs Harakat from Faala to Furla, in addition to changing the vowel sounds in the voiced verb when affixed, as well as the need for the deputy subject to indicate the gender by changing Y into T of the verb added to its end. Arabic goes farther to add expressions like Ina, Ana, tha, Lw, Kollama, Robama, etc, to change the structure of the sentences as well as the verb structure. Also, naming the intellectual concepts in both languages forms are three: wishfulness, conditional, and Choice selective.